Modulation of Gut Microbiota, Short-Chain Fatty Acid Production, and Inflammatory Cytokine Expression in the Cecum of Porcine Deltacoronavirus-Infected Chicks - Li, Hai-yan; Zhang, Hong-lei; zhao, Fu-jie; Wang, Shi-qiong; Wang, Zhi-xiang; Wei, Zhan-yong (Frontiers in Microbiology, 2020)
Porcine deltacoronavirus (PDCoV) is a novel swine enteropathogenic coronavirus that causes watery diarrhea and induces pro-inflammatory cytokine responses in piglets. Our previous research showed that the specific-pathogen-free (SPF) chicks exhibited mild diarrhea and low fecal viral shedding, along with cecum lesions after PDCoV infection. Disturbances in the homeostasis of the gut microbiota have been associated with various diseases. Our aim was to explore the effects of PDCoV infection on chick gut microbiota, short-chain fatty acids (SCFAs) production and inflammation cytokines expression in chicks, and also to investigate the relationship between gut microbiota and SCFAs or inflammation cytokines expression of the PDCoV infected chicks. The results showed that PDCoV strain HNZK-02 infection significantly altered the composition of chick gut microbiota using 16S rRNA sequencing, with the reduced abundance of Eisenbergiella and Anaerotruncus genera at 5 days post-inoculation (dpi) (P < 0.05), and an increased abundance of Alistipes genus at 17 dpi (P < 0.05). The production of SCFAs in the cecum of PDCoV HNZK-02 infected chicks, including acetic acid (AA), propionic acid (PA) and butyric acid (BA), were all decreased. The expression of inflammatory cytokines (IFN-γ, TNF-α and IL-10) was increased in the cecum tissue and serum of the PDCoV HNZK-02 infected chicks when detected by quantitative real-time PCR and ELISA, respectively. Further analysis showed significant correlation between bacterial genera and SCFAs or inflammatory cytokines expression in cecum of the PDCoV infected chicks. These findings might provide new insight into the pathology and physiology of PDCoV in chicks.